2018
DOI: 10.1038/s41467-018-04076-0
|View full text |Cite
|
Sign up to set email alerts
|

The human Vδ2+ T-cell compartment comprises distinct innate-like Vγ9+ and adaptive Vγ9- subsets

Abstract: Vδ2+ T cells form the predominant human γδ T-cell population in peripheral blood and mediate T-cell receptor (TCR)-dependent anti-microbial and anti-tumour immunity. Here we show that the Vδ2+ compartment comprises both innate-like and adaptive subsets. Vγ9+ Vδ2+ T cells display semi-invariant TCR repertoires, featuring public Vγ9 TCR sequences equivalent in cord and adult blood. By contrast, we also identify a separate, Vγ9− Vδ2+ T-cell subset that typically has a CD27hiCCR7+CD28+IL-7Rα+ naive-like phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
260
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 178 publications
(299 citation statements)
references
References 59 publications
(93 reference statements)
22
260
1
Order By: Relevance
“…9 On the contrary, IL-17 cd T cells preferentially express CCR6 and the transcription factor PLZF, which is considered to confer innate-like properties to lymphocytes. 20 The Vd2 + subset constitutes an heterogeneous population of cells, producing a range of pro-inflammatory cytokines including IFN-c, IL-17, TNF-a, IL-9, but also IL-10 depending on the setting. [14][15][16] Nevertheless, human thymic cd T cells exhibit de novo expression of type 1 transcription factors T-bet and eomesodermin, reflecting their capacity to rapidly differentiate into cytotoxic effectors producing IFN-c in response to cytokines IL-2 and IL-15.…”
Section: Introductionmentioning
confidence: 99%
“…9 On the contrary, IL-17 cd T cells preferentially express CCR6 and the transcription factor PLZF, which is considered to confer innate-like properties to lymphocytes. 20 The Vd2 + subset constitutes an heterogeneous population of cells, producing a range of pro-inflammatory cytokines including IFN-c, IL-17, TNF-a, IL-9, but also IL-10 depending on the setting. [14][15][16] Nevertheless, human thymic cd T cells exhibit de novo expression of type 1 transcription factors T-bet and eomesodermin, reflecting their capacity to rapidly differentiate into cytotoxic effectors producing IFN-c in response to cytokines IL-2 and IL-15.…”
Section: Introductionmentioning
confidence: 99%
“…The dissection of clonality via TCR analysis has, until recently, been limited by our inability to detect paired TCRγδ chains directly ex vivo for single cells. To date, paired analyses have demonstrated signatures of innate‐ and adaptive‐like T cells in the Vδ2 + Vγ9 + and Vδ2 + Vγ9 − , respectively, in human peripheral and umbilical cord blood (CB) . Analysis of TCR repertoire in chronic viral infections within patients suffering CMV reactivation following transplantation has been performed .…”
Section: Introductionmentioning
confidence: 99%
“…To date, paired analyses have demonstrated signatures of innate-and adaptive-like T cells in the Vd2 + Vc9 + and Vd2 + Vc9 À , respectively, in human peripheral and umbilical cord blood (CB). 14,15 Analysis of TCR repertoire in chronic viral infections within patients suffering CMV reactivation following transplantation has been performed. 14,16 Antigen specificity and clonal expansions from both bulk analyses of c9 + or c9 À T cells, 14,16 and from paired analyses at the single-cell level, were observed, 15 suggesting that there may be specificity for the virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mice have highlighted ‘innate‐like’ γδ T cells subsets emerging early in thymic development, bearing semi‐invariant TCRs, suggestive of a limited range of self‐ligands. Recent studies in humans have also identified that a major human γδ T‐cell population, constituting the largest subset of γδ T cells at tissue locations, follow an adaptive immunobiology . In this Special Feature of Clinical & Translational Immunology , we have invited experts in γδ T‐cell biology to provide an overview of the emerging roles of this often overlooked and unique population of T cells in health and disease (Figure ).…”
mentioning
confidence: 99%